1993
DOI: 10.1002/1098-108x(199301)13:1<41::aid-eat2260130106>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and eating disorders: A review and clinical implications

Abstract: Pregnancy and eating disorders is a subject that has received relatively little attention in the literature. Yet, several serious complications have been found in both the mother and the fetus when a woman with an eating disorder becomes pregnant. In this paper the literature is reviewed for both anorexia nervosa and bulimia nervosa and suggestions for future research are offered. Clinical implications for the treatment of the pregnant eating disordered patient are discussed. © by John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 33 publications
0
33
0
2
Order By: Relevance
“…As such, the extent of adolescents' adaption to pregnancy body changes is important, because body dissatisfaction in pregnancy is associated with many harmful consequences to both the mother and the fetus. 2,18,19 For example, the adult literature has shown that pregnant women who experience negative body image are more likely to engage in unhealthy eating, dieting, and purging behaviors as compared to pregnant women who are satisfied with their bodies. 18 Also, unhealthy weight control behaviors have been associated with poor pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the extent of adolescents' adaption to pregnancy body changes is important, because body dissatisfaction in pregnancy is associated with many harmful consequences to both the mother and the fetus. 2,18,19 For example, the adult literature has shown that pregnant women who experience negative body image are more likely to engage in unhealthy eating, dieting, and purging behaviors as compared to pregnant women who are satisfied with their bodies. 18 Also, unhealthy weight control behaviors have been associated with poor pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…18 Also, unhealthy weight control behaviors have been associated with poor pregnancy outcomes. 2,18,19 Unfortunately, there is no adolescent research examining the effects of poor body image in pregnancy on eating and dieting behavior and the secondary effects on pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors aiACmpni.no.ni.hAymnywA,,hnvAnoCmpnc.no.hAmn.hAi'i ability to parent effectively and the way in which feeding is carried out (Franko et al, 1993;Hampson et al, 2010;Ozmen et al, 2007;Patel et al, 2002;Reba-Harreleson et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…No entanto, os técnicos de saúde podem não conseguir identificar as perturbações do comportamento alimentar, já que (a) os pacientes apresentam relutância em revelar a sua problemática, mesmo quando o diagnóstico se refere à sua história passada (Edelstein & King, 1992;Franko & Spurell, 2000;Franko & Walton, 1993;Lemberg & Phillips, 1989;Mitchell-Gieleghem et al, 2002;Newton & Chizawsky, 2006;Norre, Vandereycken, & Gordts, 2001;Stewart, 1992), normalmente associado a sentimentos de vergonha (Newton & Chizawsky, 2006); (b) muitas vezes, os sintomas mais visíveis, nomeadamente na anorexia nervosa (como é o caso da amenorreia), não estão presentes no período gravídico; (c) nem sempre as perturbações são evidenciadas pelo aspecto físico, como no caso da bulimia nervosa, que abrange indivíduos com qualquer peso (Newton & Chizawsky, 2006); (d) outros sintomas podem esconder o diagnóstico (como a hiperemese gravídica, que pode esconder bulimia nervosa; Lingam & McCluskey, 1996); e (e) as perturbações são egosintónicas, podendo traduzir-se em negação da perturbação (Newton & Chizawsky, 2006). Além desta omissão frequente aos clínicos, as mulheres com perturbações do comportamento alimentar na gravidez podem inclusive esconder a perturbação ou tentar minimizar alguns comportamentos específicos aos cônjuges, familiares, amigos ou terapeuta.…”
Section: Técnicos De Saúde: Avaliação E Intervençãounclassified